Computational and statistical methodologies for ORFeome primary structure analysis - Moura, Gabriela (2020)
Codon usage and context are biased in open reading frames (ORFs) of most genomes. Codon usage is largely influenced by biased genome G+C pressure, in particular in prokaryotes, but the general rules that govern the evolution of codon context remain largely elusive. In order to shed new light into this question we have developed computational, statistical and graphical tools for analysis of codon context on an ORFeome wide scale. In here, we describe these methodologies in detail and show how they can be used for analysis of ORFs of any genome sequenced.